Split-Belt Treadmill Adaptation Transfers to Overground Walking in Persons Poststroke - Reisman, Darcy S. (2009)
BACKGROUND AND OBJECTIVE: Following stroke, subjects retain the ability to adapt interlimb symmetry on the split-belt treadmill. Critical to advancing our understanding of locomotor adaptation and its usefulness in rehabilitation is discerning whether adaptive effects observed on a treadmill transfer to walking over ground. We examined whether aftereffects following split-belt treadmill adaptation transfer to overground walking in healthy persons and those poststroke. METHODS: Eleven poststroke and 11 age-matched and gender-matched healthy subjects walked over ground before and after walking on a split-belt treadmill. Adaptation and aftereffects in step length and double support time were calculated. RESULTS: Both groups demonstrated partial transfer of the aftereffects observed on the treadmill (P < .001) to overground walking (P < .05), but the transfer was more robust in the subjects poststroke (P < .05). The subjects with baseline asymmetry after stroke improved in asymmetry of step length and double limb support (P = .06). CONCLUSIONS: The partial transfer of aftereffects to overground walking suggests that some shared neural circuits that control locomotion for different environmental contexts are adapted during split-belt treadmill walking. The larger adaptation transfer from the treadmill to overground walking in the stroke survivors may be due to difficulty adjusting their walking pattern to changing environmental demands. Such difficulties with context switching have been considered detrimental to function poststroke. However, we propose that the persistence of improved symmetry when changing context to overground walking could be used to advantage in poststroke rehabilitation.